Chemesthesis : chemical touch in food and eating - McDonald, Shane T.; Bolliet, David; Hayes, John (John Wiley & Sons, Inc., 2016)
Chemesthesis: Chemical Touch in Food and Eating surveys the modern body of work on chemesthesis, with a variety of contributors who are well known for their expertise on the topic. After a forward by John Prescott and an introduction by Barry Green (who originally coined the term chemesthesis 25 years ago), the book moves on to survey chemesthetic spices and address the psychology and physiology of chemesthesis, the practical sensory and instrumental analysis, the interaction of chemesthesis with other chemical senses, health ramifications, and the application of chemesthesis in food. The major types of chemesthesis, including pungency, burning, cooling, tingling, nasal irritation, and numbing, are each covered in their own chapter. The book concludes with a look to the future.
Keywords: potraviny; senzorická analýza; foodstuffs; sensoric analysis; chemestéza; kolektivní monografie; elektronické knihy; collective monographs; electronic books